AKTIVITAS PELAKSANAAN PROGRAM COMMUNITY ENGANGEMENT SEBAGAI BENTUK CORPORATE SOSIAL RESPONSIBILITY PT.CHEVRON TERHADAP MASYARAKAT SAKAI DIDURI - Dinni Syofyanil; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Community Engangement from about CSR, As one of strategy to increase corporate image is to set up and carry out CSR program are on target. PT Chevron Pacific Indonesia as one of the companies active in the field of oil and gas trying to realize it with focus to carry out CSR program in several operational areas. This research aim to find out how CSR program in the run PT Chevron, and knowing the constrainsts of PT.Chevron in carrying that CE programs. This research used qualitative methods with a descriptive approach. The research was conducted at PGPA PT.Chevron distric in duri. With the object of research is the CE program PT. Chevron. And research subject which team manager of Policy Goverment and Public Affair (PGPA) and sakai community’s both internally and externally through pruposive sampling. Data collection techniques in this research is observation, interviews and documentation. The results of this research are that run the company’s CE program in several aspecys of life. That is economic,education and then health is related to the role of Public Relations and CSR Officer.CE Program that run the company are prepared in accordance with need and condition of public and the capability of the company itself. By carrying out CE Program as an effort to increase corporate image, PT Chevron Has been able to create good impression on the community and attract public confidence. In carrying program are constraints CE it socializatin between the two parties is considered not maximized evenly in various aspects.